2020
DOI: 10.1111/1750-3841.15341
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tea polyphenol ester with different fatty acid chain length on camellia oil‐based oleogels preparation and its effects on cookies properties

Abstract: Oleogels were prepared by emulsion template method through 3.0% tea polyphenol ester (Tp‐ester) particles with four fatty acid chain length (Tp‐laurate [C12], Tp‐myristate [C14], Tp‐palmitate [C16], and Tp‐stearate [C18]) and 2.5% citrus pectin, and then were used in cookie production as fat replacer. Effects of the fatty acid chain length on the hydrophilicity/hydrophobicity of Tp‐ester, on the appearance, microstructure, and firmness of dried products, on rheological features of oleogels, on the dynamic visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…When used as a replacement for butter in cakes, the oleogels achieved a satisfactory overall quality with hedonic scores ranging from 21.49 to 27.58, compared to a score of 32.03 for cakes made with butter. In addition, Pan et al [ 123 ] developed pectin oleogels combined with tea polyphenol ester particles of different fatty acid chain lengths, which were further used in cookie production as a fat replacer. The study found that the fatty acid chain length influenced the characteristics of the oleogels, including appearance, firmness, and gel intensity.…”
Section: Types Of Pectin Gelsmentioning
confidence: 99%
“…When used as a replacement for butter in cakes, the oleogels achieved a satisfactory overall quality with hedonic scores ranging from 21.49 to 27.58, compared to a score of 32.03 for cakes made with butter. In addition, Pan et al [ 123 ] developed pectin oleogels combined with tea polyphenol ester particles of different fatty acid chain lengths, which were further used in cookie production as a fat replacer. The study found that the fatty acid chain length influenced the characteristics of the oleogels, including appearance, firmness, and gel intensity.…”
Section: Types Of Pectin Gelsmentioning
confidence: 99%